2003
DOI: 10.1128/jcm.41.8.3851-3853.2003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Rapid PCR Assay for Diagnosis of Meningococcal Meningitis

Abstract: We compared the results of Gram staining and culture of cerebrospinal fluid to results obtained with a rapid PCR assay for the diagnosis of meningococcal meningitis in 281 cases of suspected bacterial meningitis. PCR had a sensitivity of 97% compared to a sensitivity of 55% for culture, and the PCR specificity was 99.6%. PCR results were available within 2 h of the start of the assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 14 publications
1
18
0
2
Order By: Relevance
“…In the recent past, PCR assays have been developed for the specific detection of bacteria causing meningitis such as N. meningitidis (16,21), S. pneumoniae (11,29), and S. agalactiae (10). Several studies have demonstrated the usefulness of eubacterial broad-range PCRs for the diagnosis of bacterial meningitis (3,6,13,14,23).…”
mentioning
confidence: 99%
“…In the recent past, PCR assays have been developed for the specific detection of bacteria causing meningitis such as N. meningitidis (16,21), S. pneumoniae (11,29), and S. agalactiae (10). Several studies have demonstrated the usefulness of eubacterial broad-range PCRs for the diagnosis of bacterial meningitis (3,6,13,14,23).…”
mentioning
confidence: 99%
“…Therefore, the serogroup identification of 11 isolates of the ST-1 and ST-5 complexes was repeated by sequencing the siaD gene as described previously. 31 The nucleotide sequence and serogrouping data were consistent.…”
Section: Lineages Found In Specified Periodmentioning
confidence: 63%
“…Lu et al [8], reported a sensitivity of 92.3%. Richardson et al [18], have described a PCR assay for the diagnosis of meningococcal meningitis, which had a sensitivity of 97% as compared to a CSF culture sensitivity of 55%. Schuurman et al [17], found broad range PCR was more useful in meningitis with sensitivity of 86%, specificity of 97%, positive predictive value of 80% and negative predictive value of 98% as compared to conventional culture.…”
Section: Discussionmentioning
confidence: 99%